PENGARUH KOMPOS KULIT BUAH KAKAO DI MEDIUM PODSOLIK MERAH KUNING (PMK) TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) - Jan Eko Saputra P; Sampurno ' '; Islan ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to determine the effect of compost pod husks and bark compost dose of the best cacao in the medium Red Yellow Podzolic  on the growth of seedlings of oil palm (Elaeis guineensis Jacq). This research was conducted at the experimental farm, Faculty of Agriculture, University of Riau Jl. Bina Widya Baru Simpang KM 12.5, Tampan, Pekanbaru. This study was conducted over four months starting from June 2015 to September 2015. This study was conducted experimentally using a completely randomized design (CRD), which consists of 5 treatments and each treatment was repeated 4kali thus obtained 20 experimental units, each unit consisting experiment of 2 seeds. The total number of 40 seeds and seedlings observations were made at all. Parameters measured were as height seed, in the number of leaves, the increase in diameter stump, root volume, dry weight ratio of canopy seeds and roots. It can be concluded that composting pod husks on oil palm seedlings in the medium PMK significant effect on the increase seedling height, leaf number, root volume and dry weight of seedlings, but the effect is not noticeable to the diameter of the stump and roots canopy ratio. At doses of compost pod husks 125 g/polybag provide the best dose results in increase in the number of leaves, root volume and dry weight of seedlings. As for the high increment dose of compost plant pod husks best was 50 g/polybag. While on the increase in diameter tubers and roots canopy ratio dose of 100 g/polybag is the best dose.   Keywords: Palm Oil, Cocoa Fruit Feel Compost, Red-Yellow Podzolic Soil